MANAGEMENT OF INCLUSIVE EDUCATION CLASSES IN ONE OF THE ELEMENTARY SCHOOL IN JAMBI PROVINCE - Firman, Firman (Dinasti Publisher, 2020)
This study aimed to obtain a general overview of the implementation of the inclusion learning process in one elementary school in Jambi Province. This research was a qualitative research. Data collected through observation, interviews, and documentation studies. Data analysis referred to the Miles and Huberman model, which is carried out in three phases: the first phase was a preliminary analysis; the second stage was done while collecting data on the site, and the third was done after completing data collection. Data analysis is performed through category development, data reduction, data presentation, drawing conclusions, and verification. The data was conducted in September 2017. The results of this study indicated that the management of inclusive education classes is divided into two categorizes, there are: the seating arrangement and special needs students’ study time.